Digital Transformation and Organizational Culture Change in the Post-pandemic Era: A Structural Equation Modelling Approach in a Diverse Regional Context - Eldin, Anwar Yahia Shams; Aloui , Leila (International Review of Management and Marketing, 2026)
The acceleration of digital transformation spurred by the COVID-19 pandemic has reshaped organizational culture. In this context, knowledge acquisition became vital for adapting to new technologies and work models. This study examines digital transformation’s impact on organizational culture, with a focus on analysing knowledge acquisition as a mediator both during and after the pandemic. Adopting a descriptive-analytical approach, data were gathered from 373 organizations across five continents and various industries. The study captures a broad spectrum of cross-regional and sectoral adaptation practices by targeting professionals with direct experience in digital transformation initiatives during and post-COVID-19. The results show that digital transformation significantly influences organizational culture transformation through its effect on knowledge acquisition. Moreover, quantitative evidence indicates that the transformation of IT capabilities directly and positively affects both knowledge acquisition and organizational culture transformation. However, IT resources alone do not directly impact this transformation. Additionally, knowledge acquisition significantly mediates the relationship between IT resources transformation, IT capabilities, and organizational culture transformation. The findings underscore the importance of strategically integrating knowledge acquisition processes with digital transformation initiatives to effectively adapt organizational cultures to emerging digital contexts. Organizations aiming for sustained competitive advantage should prioritize enhancing IT capabilities and systematically acquiring and managing knowledge to drive cultural adaptability and resilience.